Benefits from the cooperation of non-governmental organizations with enterprises and durability of cooperation - Mackiewicz, Hanna; Spodarczyk, Edyta (Zielona Góra: Faculty of Economics and Management Press)
The article attempts to determine the benefits that are the basis for permanent business cooperation with non-governmental organizations (NGOs). These benefits are presented on the basis of literature, analyzed case studies and from the point of view of business representatives and non-governmental organizations who shared their practical experience in this field with the authors of the article.
Keywords: cross-sectoral cooperation; non-governmental organizations; enterprises